Hepatitis C virus eradication with direct‐acting antiviral improves insulin resistance. Issue 2 (2nd December 2019) - Russo, Francesco Paolo; Zanetto, Alberto; Gambato, Martina; Bortoluzzi, Ilaria; Al Zoairy, Ramona; Franceschet, Enrica; De Marchi, Federica; Marzi, Luca; Lynch, Erica Nicola; Floreani, Annarosa; Farinati, Fabio; Schaefer, Benedikt; et al.
Abstract: Sustained virological response (SVR) after interferon‐based therapy is associated with improvement of insulin resistance (IR) in HCV‐infected patients. Few data are available in the direct‐acting antivirals (DAAs) era, especially in cirrhotic patients. We prospectively evaluated the long‐term effect of DAAs on IR. Patients treated with DAAs between May 2015 and December 2016 in 3 tertiary care centres were recruited. Patients with diabetes were excluded. Biochemical and virological data were collected at baseline, 12/24/48 weeks (W) after the end of therapy (EOT). Presence of IR was defined by a 'homeostasis model assessment index for IR' [HOMA‐IR])> 2.5. Liver fibroscan was performed at baseline, at 24/48W after EOT. Hundred and thirty‐eight patients were enrolled (mean age 58 years, M/F 85/53, GT1 61%, 68.8% cirrhotic). Sixty‐eight patients (94/138) had IR. Patients with IR had significantly higher stiffness than patients without it (23 ± 12 vs 15 ± 8; P  < .0001). SVR12 was achieved in 135 (98%) patients, and 124 (90%) patients reached the 48W post‐EOT. At this time point, the percentage of patients with IR significantly decreased to 49% ( P  = 0, 01). HOMA‐IR was significantly lower than baseline (1.8 vs 3; P  < .001), and this was related to a significant reduction of insulin level (11.7 ± 6.3 vs 16.4 ± 8.3). High BMI was associated with a significantly lower probability of achieving a non‐IR status at 24W ( P  = .05) and 48W ( P  = .03).In conclusion, SVR following DAAs led to a significant reduction of IR, even in patients with cirrhosis. Nevertheless, IR can persist after the achievement of SVR, especially in patients with high BMI.